BEBERAPA FAKTOR YANG BERHUBUNGAN DENGAN PREFERENSI PENOLONG PERSALINAN PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS PIMPINAN KECAMATAN TELUK KERAMAT KABUPATEN SAMBAS - Mardjan, Mardjan; Taufik, M (Fakultas Ilmu Kesehatan Universitas Muhammadiyah Pontianak, 2016)
Childbirth is a risky period for pregnant women who experience complications that can increase the risk of maternal and infant mortality. Pimpinan public health center had the lowest coverage (61,3%) of delivery by health attendants in Sambas district. This study aimed at testing the factors related to the preferencw of birth attendents at work area of Pimpinan Health Center, Kecamatan Teluk Keramat Kabupaten Sambas.Using analytical survey design and cross sectional approach, as many as 78 respondents participated in this study. They were selected by using simple random sampling. The data were tested by using parametric chi square at 95% significant level.The study revealed that there were significant correlation of educational attainment (p value = 0,006), family income (p value = 0,000; RP = 9,739, 95% CI = 2,599-36,490), knowledge (p value = 0,000; RP = 7,130 95% CI = 2,582-19,684), antenatal care visits (p value = 0,000; RP = 7,912, 95% CI = 2,703-23,162), culture (p value = 0,000; RP = 21,956, 95% CI 6,602-73,015). The variables that didn’t correlate with the preference of birth attendents were health insurance membership (p value = 0,179) health access (p value = 0,787) and widwife availability (p value = 0,377). In other words, the factors related to the preference of birth attendents were aducation, family income, knowledge, ANC visit and culture.From the findings, Pimpinan health center is encouraged to approach the public figure and the religious leaders to welcome the midwives placement in their villages. In addition, the midwives need to motivate the pregnant women to ask for health attendants assistance in giving birthKey words : Health attendants, Knowledge, Culture, ANC visit, Education